Developing a new phosphorus-carbon bond synthesis - Ng, Yong Xiang (2016)
This thesis is about developing a new phosphorus-carbon bond synthesis based on electrophilic terminal phosphinidene chemistry and finding application for this methodology. The first chapter gives a brief account of the general methods in forming phosphorus-carbon bonds. The second chapter details the works of the author on using the reaction of electrophilic terminal phosphinidene complexes with arylboronic acids in presence of potassium phosphate to form phosphorus-carbon bond. Preliminary mechanistic study was carried out, and the results tentatively suggest that the reaction proceeds via the insertion of phosphinidene complex into the boron-oxygen bond of arylboronic acid, followed by a 1,2-migration of the aryl group onto the phosphorus atom. The third chapter is based on exploring and expanding the scope and application for this new P-C bond. It was found out that the reaction pathway of terminal phosphinidene complexes and alkenylboronic acids can be altered by potassium phosphate. In the absence of phosphate, [1+2] cycloaddition proceeds to give phosphirane complexes; P-C bond formation proceeds in the presence of phosphate to give secondary alkenylphosphine complexes. Computations were made to understand this shift in reaction. Attempts to synthesise other organophosphorus compounds were also made.